A multifunctional separator based on scandium oxide nanocrystal decorated carbon nanotubes for high performance lithium–sulfur batteries. Issue 12 (18th March 2020) - Xu, Jun; Zhang, Qi; Liang, Xin; Yan, Jian; Liu, Jiaqin; Wu, Yucheng
Abstract : Rare earth oxides, for example scandium oxide, may open up a new prospect towards the development of advanced Li–S batteries and other energy storage systems. Abstract : Rare earths (REs) and their oxides have aroused worldwide interest because of their unusual and remarkable properties, which mainly stem from the unique 4f orbital of REs. Research on their potential applications in electrochemical energy storage devices is just budding, and needs bold and active exploration. Here, a multifunctional Sc2 O3 @CNT-coated separator was developed and introduced into the Li–S battery system, simply by coating a thin and lightweight capping layer of a synthesized composite of Sc2 O3 nanocrystal decorated carbon nanotubes (Sc2 O3 @CNTs) over one side of a commercial separator. The Li–S battery based on the Sc2 O3 @CNT-coated separator possesses very important properties, including high capacity, superior cycling stability, impressive rate performance, favorable anti-self-discharge capabilities, and greatly mitigated anode corrosion. Theoretical computation and experimental results demonstrate that such outstanding electrochemical properties originate from the synergy of CNTs and Sc2 O3, which enables the Sc2 O3 @CNT-coated separator to achieve an optimal balance of multiple functions: (1) physically blocking polysulfide migration and acting as an upper current collector, (2) chemically anchoring polysulfide species, and (3) catalytically promoting the conversion of sulfur species into Li2 S2 /Li2 S. This work first applies Sc2 O3 to Li–S batteries, and the encouraging results show great potential of rare earth oxides for producing high-performance energy storage devices.